2020
DOI: 10.3390/ijerph17207673
|View full text |Cite
|
Sign up to set email alerts
|

Roma Ethnicity and Sex-Specific Associations of Serum Uric Acid with Cardiometabolic and Hepatorenal Health Factors in Eastern Slovakian Population: The HepaMeta Study

Abstract: Background: Health characteristics associated with uric acid (UA) in the Roma minority remain less well known. The study sought to determine the ethnicity- and sex-specific associations of serum UA with health factors in Eastern Slovakian Roma and non-Roma populations. Methods: Data from the comparative cross-sectional HepaMeta study conducted in Slovakia in 2011 were used. The study enrolled 452 Roma subjects (35.2% men) and 403 non-Roma individuals (45.9% men) aged 18–55 years. Results: All study parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…However, no independent correlation was shown between UA and the risk of NAFLD after adjusting for confounding factors, which suggested that the effect of UA may not be direct but indirect through other risk factors for NAFLD ( 44 ). This study showed that UA levels were correlated with serum ferritin, and the mechanism may be via inflammation induced by UA through the p38 mitogen-activated protein kinase, cyclooxygenase-2, and chemokine cyto-chemotactic protein-1 signal pathway ( 45 ).…”
Section: Discussionmentioning
confidence: 91%
“…However, no independent correlation was shown between UA and the risk of NAFLD after adjusting for confounding factors, which suggested that the effect of UA may not be direct but indirect through other risk factors for NAFLD ( 44 ). This study showed that UA levels were correlated with serum ferritin, and the mechanism may be via inflammation induced by UA through the p38 mitogen-activated protein kinase, cyclooxygenase-2, and chemokine cyto-chemotactic protein-1 signal pathway ( 45 ).…”
Section: Discussionmentioning
confidence: 91%
“…Recently, research of Roma health has focused on chronic illness and risk factors as determinants of mortality. Recent evidence suggests that the Roma population is at increased cardiovascular and metabolic risk and highlights the need for further investigations on the prevalence of cardiovascular risk factors among Roma people that would facilitate the diagnosis and would help to the development of effective strategies for CVD prevention among Roma population (6,24).…”
Section: Discussionmentioning
confidence: 99%
“…One animal study revealed that estrogen in the mouse model may regulate the expression or activity of UA transporters, specifically ABCG2 and SLC2A9, and this regulation increases UA excretion via renal proximal tubules and even small intestines [12]. The HepaMeta Study demonstrated that SUA level is related to gender, and higher SUA was noted in Roma males than in females, accompanied by elevated CRP and serum ferritin, as a marker of cardiovascular risk [13]. They pinpointed that females benefited from estrogen itself to prevent hyperuricemia and even gouty attack.…”
Section: Discussionmentioning
confidence: 99%